Identifikasi Penanda SSR yang Berasosiasi dengan Bobot Tandan Buah Kelapa Sawit (Elaeis guineensis Jacq.) - Yono, Dwi; Wahyu, Yudiwanti; ,, Sobir; Toruan-Mathius, dan Nurita (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Oil palm is a perennial oil crop that contribute the most important source of vegetable oil in the world. Oil palm breeding cycle take a long period, therefore molecular marker-assisted selection (MAS) is required to shorten the selection time. This MAS require the associated marker to desired trait, particularly for yield and the component that as a complex trait and depend on genetic background. The aim of this study was to obtain SSR marker that associated with average of bunch weight (ABW). Plant material was used in this study is Tenera population derived from Deli Dura x AVROS Pisifera. Seven SSR markers from public database were associated to ABW trait. Molecular data analysed for SSR markers profile which consisted of allelic diversity, heterozygosity level, and polymorphism information content (PIC). Association between SSR markers to ABW traits was performed with single marker analysis using one way analysis of variance. The results showed that SSR markers were able to amplify DNA with two to three number of alleles with the average of 2.3 alleles per locus. ABW trait for this population was significantly associated with mEgCIR3428 marker. This marker may be used in the selection of Deli Dura and AVROS Pisifera palm on the next selection cycle.Keywords: Average of bunch weight, AVROS Pisifera, Deli Dura, single marker analysis